223k views
2 votes

(2)/(3) k - (k + (1)/(4)) = (1)/(12)k + (4)/(12) \\ \\

User Intekhab
by
6.8k points

2 Answers

3 votes

Answer:

use pemdas

Explanation:

User Riccardo Bucco
by
6.4k points
3 votes

Firstly, foil -(k + 1/4) (think of the minus sign as -1):


(2)/(3)k-k-(1)/(4)=(1)/(12)k+(4)/(12)

Next, combine like terms:


-(1)/(3)k-(1)/(4)=(1)/(12)k+(4)/(12)

Next, we have to add 1/3k on both sides, but first we have to find the LCD, or lowest common denominator, of 3 and 12. To do this, list the multiples of both and the lowest one they share is their LCD. In this case, the LCD is 12. Multiply both sides of -1/3 by 4/4 and 1/12 by 1/1:


-(1)/(3)* (4)/(4)=-(4)/(12)\\\\(1)/(12)* (1)/(1)=(1)/(12)\\\\-(4)/(12)k-(1)/(4)=(1)/(12)k+(4)/(12)

Now add 4/12k on both sides of the equation:


-(1)/(4)=(5)/(12)k+(4)/(12)

Next, to subtract 4/12 on both sides we need to find the LCD of 4 and 12. It's the similar process as we did with 12 and 3. This time the LCD is also 12. Multiply both sides of -1/4 by 3/3 and 4/12 by 1/1:


-(1)/(4)* (3)/(3)=-(3)/(12)\\\\(4)/(12)* (1)/(1)=(4)/(12)\\\\-(3)/(12)=(5)/(12)k+(4)/(12)

Now subtract 4/12 on both sides:


-(7)/(12)=(5)/(12)k

Lastly, multiply both sides by 12/5, and your answer will be:


-(84)/(60)=-(7)/(5)=k

User Mavriksc
by
5.7k points